2000
DOI: 10.1097/00007632-200008150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Motion in Lumbar Functional Spine Units During Side Bending and Axial Rotation Moments Depending on the Degree of Degeneration

Abstract: A reduced lumbar disc height in radiographs seems to be associated with fissure formation in the disc. In this case, the range axial rotation after torque is increased in comparison with cases with less degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 15 publications
5
67
0
2
Order By: Relevance
“…An individualized analysis of each movement shows that the largest increases are detected in axial rotation mobility, in agree with [13,15]. Increased mobility is also more pronounced in extension, which is in agreement with [16,24].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An individualized analysis of each movement shows that the largest increases are detected in axial rotation mobility, in agree with [13,15]. Increased mobility is also more pronounced in extension, which is in agreement with [16,24].…”
Section: Discussionsupporting
confidence: 77%
“…Some authors found an increased range of motion [13], particularly in rotational movements, flexion-extension movements, and combined lateral bending and rotation movements [14]. In [15] is described an increased range of motion especially in axial rotation. In [16] an increase of vertebral displacement and mobility in flexion and extension is found in a group of patients with disc degeneration.…”
Section: Introductionmentioning
confidence: 98%
“…The hypothesis of increased flexibility for early, mildly degenerated discs was tested in numerous in vitro studies. Some papers have reported an increment in spinal flexibility for mild degeneration [20,41,63] while other investigations have found either an increase in spinal stiffness with progressing degeneration [37,45,78] or a combination of both [50]. Tanaka et al [63] found maximal flexibility in axial rotation in the lower lumbar spine for the grade III of the Thompson scale [64], whereas minimal changes in the spine motion were found in flexion, extension and lateral bending.…”
Section: Flexibilitymentioning
confidence: 99%
“…Both papers showed reduced mobility for severely degenerated spines (grade V). Krismer et al [41] did not analyze flexion-extension, but found increased flexibility of lumbar specimens in axial rotation and lateral bending starting from grade III. On the contrary, a recent study [9] reported increased range of motion only in axial rotation for severely degenerated specimens (grade IV, V), whereas in flexionextension and lateral bending disc degeneration was correlated with decreased flexibility.…”
Section: Flexibilitymentioning
confidence: 99%
“…Flexibility tests up to 8.5 Nm (Krismer et al 2000) and compression up to 1300 N (Lin et al 1978) were conducted without deterioration of the disc. The first loading consisted in 5 cycles of compression up to 1000 N were applied at 2000 N/min loading rate via a servohydraulic device (MTS, Bionix, USA).…”
Section: Parameters Identification Against Biomechanical Testsmentioning
confidence: 99%